Centaurea peltieri (Asteraceae), a new endemic species from the Oriental High Atlas of Morocco - Homrani Bakali, A.; Susanna, A. (Phytotaxa, 2021)
Centaurea peltieri (C. sect. Melanoloma) is described and illustrated as a new endemic species from the Oriental High Atlas of Morocco. The morphology of involucral bracts is the discriminant feature separating it from other closely related species of the section.